CODEBOOK ENHANCEMENT FOR VECTOR QUANTIZATION USING MINMAX VALUES FOR IMAGE COMPRESSION - S, Vimala (ICTACT journal on image and video processing, 2013)
Vector Quantization (VQ) is one of the Lossy Image Compression Techniques. Vector Quantization comprises of three different phases: Codebook Generation, Image Encoding and Image Decoding. The efficiency of VQ depends on the quality of the codebook. In this paper, we have proposed a novel idea for improving the quality of codebook. The codebook is populated with high detail blocks, with which the edges of the objects in an image can be preserved. The high detail blocks are identified based on the maximum and minimum pixel values of the blocks. K-Means clustering method is also used to improve the quality of the codebook. The quality (PSNR) of the reconstructed images by the proposed method is better when compared to that of few existing codebook generation techniques. Standard images are used to test the performance of the proposed method.